Dreams derailed: An investigation into the experiences of travel cost burdens for female commuters who are low-income earners - Fester, Carlyn Joy (Department of Civil Engineering, 2019)
South African national transport policies, legislation and frameworks, as guided by the 1996 White Paper on National Transport Policy, have committed to providing a public transport system that equitably enables citizens to affordably access the goods, services and opportunities that are essential for their well-being. However, two decades after the introduction of the White Paper, quantitative studies have found that in Cape Town, lower-income households continue to experience a negative commute experience and still spend a disproportionate amount of time and money on travel in relation to higher-income households. Further, no studies have investigated what the user experience means in the lives of the commuters who are low-income earners and how these commuters must manage their travel times and travel costs in the South African context. This rich information is required as a critical input into policy evaluations and the design of appropriate user-focused policies that are founded on an authentic understanding of user needs and user experiences. In this study, a qualitative approach was employed to investigate the commute experiences of seven Cape Town women who are low-income earners. The findings suggest that while commuter rail presents the most affordable mode of travel for respondents, the service is subject to significant disruptions which result in substantial, unexpected, and unplanned-for travel cost and travel time expenditure. This unexpected expenditure adversely impacts household travel and time budgets and respondents must adjust these budgets accordingly to the disadvantage of their household consumption and personal activities. Furthermore, while commuting, respondents have all experienced fear of crime, bearing witness to criminal activity or being the victim of criminal activity. In general, all respondents reported a negative and frustrating commute experience that differs significantly from the user-focused, affordable and time-efficient public transport service that the 1996 White Paper on National Transport Policy had promised to deliver. The study recommends renewed emphasis on integrated land-use and transport planning that reduces trip distances, prioritisation of investment in public transport infrastructure, fare and ticketing integration, restructuring of public transport subsidy frameworks and increased focus on security through visible law enforcement and lighting.